Exploring the spatial patterns and influencing factors of rural tourism development in Hainan Province of China - Xiao Kun; Wahid Ullah; Liu Dejun; Wang Ziyun (Scientific Reports)
Abstract Hainan Province is a major domestic tourism destination in China, with rural tourism playing a key role in its development. This study analyzes the spatial distribution of 154 rural tourism sites across Hainan, examining regional balance, hotspots, and influencing factors such as transportation infrastructure, economic conditions, and A-level tourist attractions. Results show a clear spatial clustering of sites, with a strong concentration in the east and more dispersed patterns in the west. Economic growth and tourism sector development are identified as key factors influencing the “coconut-level” ratings. The study offers policy recommendations to promote sustainable rural tourism, including leveraging regional advantages, enhancing transportation connectivity, and improving tourism services and infrastructure. It also calls for investment in grassroots tourism projects and strengthening regional complementarity to foster balanced and equitable growth. These findings provide valuable insights for policymakers and tourism planners seeking to integrate rural tourism into broader sustainable development strategies.